Analyzing Privacy Concern and Technology Anxiety as Determinants of Web-Based Laporkitong Adoption Level: UTAUT 2 Perspective - Rahakbauw, Sitti Mardiah; Inan, Dedi I.; Juita, Ratna (Jutisi : Jurnal Ilmiah Teknik Informatika dan Sistem Informasi, 2024)
The adoption rate of the web-based Laporkitong application is uncertain, necessitating research to optimize its usage. The objective of this study is to identify the influential factors in the utilization of web-based Laporkitong, employing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) method with the addition of variables such as technology anxiety and privacy concern, measured using Partial Least Square Structural Equation Modeling (PLS-SEM). Data collection involved 203 respondents through online questionnaires distributed over four weeks. The analysis revealed that out of the seven measured factors determining adoption rates, only performance expectancy, social influence, facilitating condition, and behavioral intention significantly influenced the adoption level. The coefficient of determination (R2) indicated that the independent variables used were sufficiently significant in predicting Use Behavior, at 72.2%, Consequently, the effort expectancy, social influence, facilitating conditions, and behavioral intentions emerged as crucial determinants shaping the adoption level of the web-based Laporkitong application among the people of West Papua.Keywords:  Laporkitong; Partial Least Square Structural Equation Modeling; Privacy Concern; Technology Anxiety; UTAUT 2AbstrakTingkat adopsi aplikasi Laporkitong berbasis website belum dipastikan sehingga perlu dilakukan penelitian untuk mengoptimalkan penggunaannya. Tujuan dari penelitian ini untuk mengetahui faktor-faktor yang memiliki pengaruh dalam penggunaan web-based Laporkitong dengan metode Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) dengan penambahan variabel Technology Anxiety dan Privacy Concern yang diukur menggunakan Partial Least Square Structural Equation Modelling (PLS-SEM). Pengumpulan sebanyak 203 responden dilakukan dengan menyebar kuesioner online selama empat minggu. Hasil analisis dari tujuh faktor penentu tingkat adopsi yang diukur, hanya performance expectancy, social influence, facilitating condition, dan behavioral intention yang berpengaruh      signifikan terhadap tingkat adopsi. Hasil coefficient of determination (R2) menunjukkan variabel-variabel independen yang digunakan cukup signifikan memprediksi Use Behaviour, yaitu sebesar 72,2%, sehingga dapat diketahui keuntungan, pengaruh sosial, kondisi yang memfasilitasi dan niat perilaku menjadi hal yang sangat berpengaruh dan menentukan tingkat adopsi aplikasi Laporkitong berbasis website oleh masyarakat Papua Barat.